COVID‐19 Rapid Review cross‐publisher initiative: What we have learned and what we are going to do next. Issue 3 (8th March 2021) - Hurst, Phil; Greaves, Sarah
Key points: The global crisis sparked collaboration between publishers and service providers to successfully address an immediate problem and demonstrated the possibility for future partnerships. Encouraging experts to join a reviewer pool and quickly review the preprint and journal submissions, we were able to publish COVID‐19 research more quickly. The initiative confirmed little author uptake of inter‐publisher journal transfer option. The collaboration showed wide consensus on open science practices which will ensure faster and more reliable research findings.